FAKTOR – FAKTOR YANG MEMPENGARUHI PAYMENT GATEWAY UNTUK PELANGGAN PT MORA TELEMATIKA INDONESIA (MORATELINDO) - Effendy, Evita; Zulkilfi, Zulkilfi; Derriawan, Derriawan (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2022)
This study aims to analyze the direct or indirect effect of HR and Infrastructure capabilities on the role of Payment Gateway, the influence of Risk Management in encouraging or strengthening Payment Gateway on Moratelindo Performance and all these variables on Moratelindo Company Performance. The research sample is 100 respondents who are the level managers of PT. Indonesian Telematics Mora. The sampling technique is purposive sampling. Collecting data using a questionnaire. The data analysis technique used Structural Equation Modeling (SEM) analysis which was processed with SmartPLS software. The results of the study prove that the ability of human resources and infrastructure has a significant effect on Payment Gateways and Payment Gateways have a significant effect on company performance. Meanwhile, the ability of human resources and infrastructure has a significant effect on the company's performance, but risk management on the Payment Gateway has no effect on the company's performance. The results also show the factors that affect the Payment Gateway by referring to the results of the analysis that has been done so as to improve the company's performance. Including the role of risk management variables that do not affect the relationship between Payment Gateways and company performance. The expected managerial implications are support in terms of increased rewards for outstanding HR, network expansion and procurement of equipment to support the company's overall system, improvement and renewal of the payment system to keep pace with digitalization developments, implement risk management to anticipate problems coming from customers.